A comparative study of BIM and CAD (architecture) - Khairun Nisa, Affandi (2014)
This thesis investigates the process flow of Building Information Modeling (BIM) for existing building in University Malaysia Pahang. This model was developed using Autodesk Revit 2014 (Architecture). One utilization activity which is visualization showed that, the visualization of this application is generally the simplest use of Building Information Modeling such as walkthrough. As visualization is the simplest it is also a great application because it enhances the overall outcome of any project. In conclusion, BIM technology helps to detect and solve problems. It is also increase the cooperation between the project team.